Formulation Development and Improved Stability of a Combination Measles and Rubella Live-Viral Vaccine Dried for Use in the NanopatchTM Microneedle Delivery System. Issue 8 (3rd August 2021) - Wan, Ying; Gupta, Vineet; Bird, Christopher; Pullagurla, Swathi R.; Fahey, Paul; Forster, Angus; Volkin, David B.; Joshi, Sangeeta B.
ABSTRACT: Measles (Me) and rubella (Ru) viral diseases are targeted for elimination by ensuring a high level of vaccination coverage worldwide. Less costly, more convenient MeRu vaccine delivery systems should improve global vaccine coverage, especially in low – and middle – income countries (LMICs). In this work, we examine formulating a live, attenuated Me and Ru combination viral vaccine with Nanopatch™, a solid polymer micro-projection array for intradermal delivery. First, high throughput, qPCR-based viral infectivity and genome assays were established to enable formulation development to stabilize Me and Ru in a scaled-down, custom-built evaporative drying system to mimic the Nanopatch™ vaccine coating process. Second, excipient screening and optimization studies identified virus stabilizers for use during the drying process and upon storage in the dried state. Finally, a series of real-time and accelerated stability studies identified eight candidate formulations that met a target thermal stability criterion for live vaccines (<1 log10 loss after 1 week storage at 37°C). Compared to −80°C control samples, the top candidate formulations resulted in minimal viral infectivity titer losses after storage at 2–8°C for 6 months (i.e., <0.1 log10 for Me, and ~0.4 log10 for Ru). After storage at 25°C over 6 months, ~0.3–0.5 and ~1.0–1.4 log10 titer losses were observed for Me and Ru, respectively, enabling the rank-ordering of the stability of candidate formulations. These results are discussed in the context of future formulation challenges for developing microneedle-based dosage forms containing stabilized live, attenuated viral vaccines for use in LMICs.